Storytelling: Peningkatan High Order Thinking Skills Siswa Sekolah Dasar Negeri 03 Ujung-Ujung Pabelan Semarang - Testiana Deni Wijayatiningsih; Riana Eka Budiastuti; Dodi Mulyadi; Muhimatul Ifadah; Siti Aimah; Eva Dina Mareta (Jurnal Surya Masyarakat, 2020)
Students at Public Elementary School 03 Ujung-Ujung Pabelan learned English only in extracurricular activities, where grade 4 and grade 5 were joined in one class. The learning was done by memorizing vocabulary and learning the structure of English grammar. During extracurricular activities, students were not introduced to HOTS-based storytelling, they only learned English vocabulary and structures. Based on this explanation, students needed HOTS skills in learning English so that they can stimulate critical thinking skills in responding to reading and other English language materials. But in reality, they tended to memorize vocabulary and grammar relatively. Based on this statement, our service team focuses community service on the implementation of storytelling to increase student’s HOTS at 03 Elementary School Ujung-Ujung Pabelan Semarang, which had 42 students. The service method used is the lecture method, brainstorming, storytelling practice, and evaluation of the satisfaction of community service participants. The results show that the student’s HOTS in learning to read English stories, retelling what they had read, and increasing the students' critical thinking patterns. The students become motivated to retell story in English and the students improve their critical thinking patterns.